Workshop Desain Grafis Untuk Meningkatkan Skill TIK Bagi Santri - Noe’man, Achmad; Hartanti, Dian (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
The development of digital media, especially in the field of graphic design, is increasingly popular. Graphic design is a form of visual communication by utilizing images as a medium for conveying messages, so that the information conveyed can be carried out as effectively and efficiently as possible. The Dulur Salembur Yatim Foundation consists of teenagers or school-age children so they are very enthusiastic about participating in this graphic design training. The purpose of graphic design training aims to improve the skills of both sons and daughters at the Dulur Salembur Orphanage Foundation. The teaching method presented in this graphic design training uses a demonstration method so that the presenters provide direct practice by the participants. It is hoped that after studying graphic design the participants will have graphic design skills by being able to create graphic design works according to their individual creative ideas, so that they are able to make vector images, make company logos and print banners and many other graphic design products.